PENGARUH DEBT TO ASSET RATIO, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Mariyatul Qibtiyah; Lita Permata Sari; Febri Ariyantiningsih (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
This study aims to examine the effects of the Debt to Asset Ratio (DAR), firm size, and sales growth on firm value, with profitability serving as an intervening variable. The research was conducted on food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study employed the Partial Least Squares (PLS) method using SmartPLS 3.0 software. The analysis included classical assumption tests, such as normality and multicollinearity tests, coefficient of determination analysis, structural model (inner model) evaluation, and hypothesis testing. The findings indicate that the Debt to Asset Ratio has a negative and significant effect on profitability. Meanwhile, firm size and sales growth have negative but insignificant effects on profitability. Regarding firm value, the Debt to Asset Ratio has a negative but insignificant effect, whereas firm size has a positive but insignificant effect. In contrast, sales growth has a positive and significant effect on firm value, and profitability also exerts a positive and significant influence on firm value. Furthermore, the indirect effect analysis reveals that the Debt to Asset Ratio and firm size have negative but insignificant effects on firm value through profitability. Similarly, sales growth has a positive but insignificant indirect effect on firm value through profitability as an intervening variable.